Implement finite scheduling for downhole equipment product line using Adexa - Guo, Yuming (2014)
Computer based scheduling systems have been becoming more and more popular in today’s manufacturing companies. These systems retrieve shop floor data from the Enterprise Resource Planning (ERP) systems and then create optimized finite capacity schedules, which reduce the manual scheduling effort significantly. Without such systems, the planners need to spend much more time to make the production schedules manually. In this thesis, the implementation of Adexa, which is a computer based scheduling system, was carried out in Schlumberger. This project focuses on the shop floor process modelling and data collection of the pump assembly process. The methodology of this project will be used as a framework to model the manufacturing process for other equipments and their components.